Airway network management using Braess’s Paradox - Ma, Chunyao (2020)
The ever increasing demand for air travel is likely to induce air traffic congestion which will elicit great economic losses. In the presence of limited airspace capacity as well as the saturated airway network, it is no longer practicable to mitigate air traffic congestion by adding new airways/links. In this paper, we provide a “counter-intuitive” perspective towards air traffic congestion mitigation by removing airways/links from a given airway network. We draw inspiration from Braess’s Paradox which suggests that adding extra links to a congested traffic network could make the traffic more congested. The paper explores whether Braess’s Paradox occurs in airway networks, or more specifically, whether it is possible to better distribute the flow in an airway network by merely removing some of its airways/links. In this paper, We develop a method for Braess’s Paradox detection in any given airway network. To validate the efficacy of the method, a case study is conducted for the South-East Asia airspace covering Singapore airway network, by using 6 months of ADS-B data. The results show that Braess’s Paradox does occur in airway networks and the proposed method can successfully identify the airway network links that may cause it. The results also demonstrate that, upon removing such links, the total travel time for a given day traffic at a given flight level, was reduced from 8661.15 min to 8328.64 min, a reduction of 332.5 min. This amounts to a saving of 3.8% in travel time.